Modular structured multilevel inverter as active power filter with unified constant-frequency integration control - Lim, Pei Yi (2005)
The usage of power electronics-based loads is increasing rapidly in recent years. The harmonic and reactive current produced by these nonlinear loads to the common coupling point at where they are connected have caused low power factor, low efficiency and harmful electromagnetic interference to neighborhood appliances. The shunt active power filter (APF) is the most common method being employed to produce harmonic current component that cancel the harmonic current from nonlinear load so that the AC main current is sinusoidal. This project presents a Modular Structured Multilevel Inverter (MSMI) as APF with Unified Constant Frequency Integration (UCI) control scheme. This scheme employs an integrator with reset as its core component to generate triangular carrier waveform. Some logical devices such as flip flop and comparators are utilized to produce switching signal to the multilevel inverter. The proposed configuration of MSMI APF with UCI control will be able to achieve unity power factor correction and low Total Harmonic Distortion (THD). Meanwhile, no sensor is required to detect the load and APF current for reference current generation as other previously proposed control method, so that the complicated digital computation can be avoided. MSMI was selected as the power converter because modularized circuit layout is possible for MSMI, which brings the convenience for future expansion in order to achieve higher power ratings for the APF system. Generally, the entire system is simple, robust and reliable. Proposed APF configuration will be compared with the conventional APF for justification of its performance.